Respuesta :

32 - 6x + 7x = -15 + 28 equals x = -19.

First, simplify 32 - 6x + 7x to 32 + x. / Your problem should look like: 32 + x = -15 + 28.
Second, simplify -15 + 28 to 13. / Your problem should look like: 32 + x = 13.
Third, subtract 32 from both sides. / Your problem should look like: x = 13 - 32.
Fourth, simplify 13 - 32 to -19. / Your problem should look like: x = -19, which is your answer. 

[tex]32\underbrace{-6x+7x}_{-6x+7x=1x}=\underbrace{-15+28}_{=28-15=13}\\\\32+1x=13\ \ \ \ \ |subtract\ 32\ from\ both\ sides\\\\32-32+x=13-32\\\\\huge\boxed{x=-19}\\\\check:\\L_S=32-6(-19)+7(-19)=32+114-133=146-133=13\\R_S=-15+28=13\\\\correct\ :)[/tex]